Evaluating Service Quality and Business Outcomes Post-Pandemic: Perspective From Hotels in Emerging Market - Olowoporoku, Ayokunnu Adekunle; Olubiyi, Timilehin Olasoji (Program Studi Administrasi Negara Universitas Serang Raya, 2023)
The impact of the novel coronavirus has been severe, and while crises are impossible to predict, they must be anticipated and planned for in business. However, less is known about the preparedness of emerging markets, particularly in the hospitality industry in Nigeria. Therefore this study seeks to situate the service quality debate within the emerging hotel service arena by exploring service quality and business outcomes in selected hotels within the Ogun East senatorial district, Ogun State, Nigeria. The study adopted the survey research design, which is cross-sectional. A convenience sampling technique was adopted in arriving at the respondents. A total of 232 copies of a questionnaire were received from the customers of twenty hotels in six major towns within the Ogun East senatorial district -Ijebu-Ode, Ago-Iwoye, Ijebu-Igbo, Sagamu, Ilishan-Remo, and Iperu-Remo representing 89.3% response rate. The regression analysis was carried out to test the effect of service quality on business outcomes. The main findings of the empirical study show that there is strong support for service quality to improve business outcomes in hotels. Specifically, service quality significantly impacted both competitiveness and brand recognition, the study's two measures of business outcomes. However, taken individually, the study found that tangibility as a factor showed little impact on outcomes but a strong impact on brand recognition. Similarly, service assurance significantly affected business competitiveness but only mildly impacted brand recognition. The distinct effects of service quality and business outcomes post-pandemic in Nigeria were highlighted. It also provided hotel stakeholders and owner-managers with insights on the need to enshrine service quality management in the corporate policies to reduce customer dissatisfaction and poor business outcomes. It is also essential for hotel operators to stay abreast of the current and future needs of an ever-evolving industry and to meet the demands of guests who are becoming more sophisticated. Innovation and originality are essential to the hotel industry's outcome. This is one of the first studies to provide empirical evidence of the relationship between service quality and business outcomes post-pandemic in Nigeria. The results provide new insights into this relationship and may clarify divergent results found in the literature from other climes